Conceptual mapping: active methodology in teaching-learning integrated concepts of Public Health and Epidemiology - Aita Schmitz, Carlos André (2024)
INTRODUCTION: in the Meaningful Learning Theory, concepts have hierarchy with progressive differentiation, and cross-links among them can lead to creative vision. Concept mapping (CM) uses concepts interconnected by lines with meaning, being applied at various educational levels and converges with active learning methodologies. OBJECTIVE: to use CM in the consolidation of integrated concepts of Public Health and Epidemiology in undergraduate education. METHOD: case report on the transcription – and its use in class – of a large textual volume with the Cmap Tools software, evaluated according to Novak's rules. RESULTS: 175 pages of the book The Ghost Map were summarized in an A4 size CM, without loss of essential content, guiding the instructor's discourse and allowing student review, including hypertext resources. The CM followed Novak's 4 rules, with organizational and aesthetic clarity. DISCUSSION: CM is both an objective and subjective construction, with the power of analysis and synthesis that elicits concepts and their interrelationships in a hierarchical and organized manner, unveiling knowledge in an enjoyable, creative, and aesthetic way. CONCLUSION: CM is an active learning methodology that may be applied and encouraged in all teaching-learning spaces.